Liquid-liquid phase separation induces pathogenic tau conformations in vitro - Nicholas M. Kanaan (Nature Portfolio, 2020)
Tau plays an important role in tauopathies and undergoes liquid-liquid phase separation (LLPS). The authors show that disease-related P301L mutant and phosphomimic (S199E/S202E/T205E) tau enhance LLPS in vitro at physiological levels, and using specific antibodies, that tau LLPS leads to pathological conformations such as N-terminal exposure and oligomeric species.